Implementasi Metode Mind Mapping Dalam Meningkatkan Prestasi Belajar Siswa Pada Mata Pelajaran Geografi - Sofyan Syamratulangi; Siama; Qurban Hajar (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2022)
Learning is a purposeful and controlled effort so that other people learn or there are relatively permanent changes in other people. The aims of this study are: 1) Describe the geography learning plan through the use of Mind Mapping techniques. 2) Assessing the implementation of Geography learning through the use of Mind Mapping. 3) Knowing the increase in student learning outcomes in the subject of Geography by using Mind Mapping. In this research, the approach used is qualitative research in the form of classroom action. Classroom action research (CAR) is different from ordinary research because this research has special characteristics, namely, it has cycles that begin with planning, then action, observation (as well as assessment) to reflection, this research was carried out in class X at SMAN 1 Lambu Bima District. The process of assessing learning achievement in learning using mind mapping in improving the learning achievement of class XA students in Geography lessons at SMAN 1 Lambu there is a significant change in learning outcomes, this is marked by an increase in student achievement in each cycle, namely cycle I the average value average (60.5%) the second the cycle the average value (72.6%), and the third cycle the average value (84.3%).